A cytomegalovirus DNA sequence containing tracts of tandemly repeated CA dinucleotides hybridizes to highly repetitive dispersed elements in mammalian cell genomes. - Jeang, K T (1983)
A single 880-base-pair region within the genome of simian cytomegalovirus strain Colburn contains sequences that hybridize intensely with both human and mouse total genome DNA probes. This sequence was also found in a second simian cytomegalovirus isolate and was retained in both plaque-purified virus subclones and in plasmid DNA clones containing the SalI P fragment. Cleaved genomic DNAs from several mammalian species all exhibited strong dispersed hybridization with the SalI-P probes, and over 70% of the lambda clones in a mouse genomic library plus several selected clones containing globin, 45S rDNA, or 5S rDNA genes all formed hybrids with SalI-P. The appropriate region of cytomegalovirus SalI-P contains relatively A + T-rich unique sequences interrupted by three stretches of the simple alternating dinucleotides, (CA)15, (CA)22, and (CA)21, which we show to be responsible for most of the cell-virus homology. We conclude that discrete, tandemly repeated (CA) dinucleotide tracts capable of forming left-handed Z-DNA helices punctuate mammalian genomes at greater than 10(5) copies per cell and that three adjacent copies of what appear to be a family of interspersed repetitive elements containing these (CA)n stretches are carried in the genomes of simian cytomegaloviruses.